Effect of Na and the back contact on Cu2Zn(Sn, Ge)Se4 thin-film solar cells: Towards semi-transparent solar cells. (August 2020) - Ruiz-Perona, Andrea; Sánchez, Yudania; Guc, Maxim; Khelifi, Samira; Kodalle, Tim; Placidi, Marcel; Merino, José Manuel; León, Máximo; Caballero, Raquel
Graphical abstract: Highlights: Promotion of Ge incorporation into CZTSe lattice via Na, detected by XRD and Raman. Thicker NaF layer results in higher Ge content, Eg and shorter depletion width. Nano-Mo/nano-V2 O5 /FTO as good back contact for semi-transparent kesterite devices. Semi-transparent CZTGSe-based solar cells with 5.6% efficiency. Abstract: Cu2 ZnSn1-x Gex Se4 (CZTGSe) thin films have been grown onto Mo/SLG and Mo/V2 O5 /FTO/SLG substrates using thermal co-evaporation followed by a subsequent thermal annealing. A NaF precursor layer was evaporated prior to the deposition of the kesterite absorber layer. In the samples grown on Mo/SLG, it has been found that Na promotes Ge incorporation into the Cu2 ZnSnSe4 lattice. The high concentration of incorporated Ge leads to the segregation of Sn-Se secondary phases as well as to an accumulation of Sn next to the Mo layer. The use of 12 and 16 nm NaF thick precursor layers prior to the CZTGSe deposition leads to absorber band gaps of 1.30 and 1.34 eV, and to device performances of 4.7 and 4.0%, respectively. A higher Na content, furthermore, caused the formation of bigger grains, a higher charge carrier concentration and a shorter depletion width. A 12 nm NaF precursor layer was used for the devices grown on FTO-based substrates, producing an optimal back contact that allows achieving efficiencies of 5.6% and transmittance of 30% in the near infrared range. This enhanced performance can be associated with the absence of secondary phases and Ge distribution through the absorber layer. The formation of a MoSe2 layer at the back interface in all the investigated devices seems to play a crucial role to improve the solar cell efficiency.